2022
DOI: 10.1007/s10639-022-11132-2
|View full text |Cite
|
Sign up to set email alerts
|

The dual role of humanoid robots in education: As didactic tools and social actors

Abstract: The idea of using social robots for teaching and learning has become increasingly prevalent and robots are assigned various roles in different educational settings. However, there are still few authentic studies conducted over time. Our study explores teachers' perceptions of a learning activity in which a child plays a digital mathematics game together with a humanoid robot. The activity is based on the idea of learning-by-teaching where the robot is designed to act as a tutee while the child is assigned the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Rozendaal et al (2019) ; Rozendaal et al (2020) and Ekström and Pareto (2022) have explored robotic agents (robotic ball, robotic backpack, Pepper as a social, and educational robot) playing interchangeable roles between a tool and an agent, which aligns with the design implications on the theme relating emphasized in this work. The results and design implications of this work suggest that a social robot should be able to transition between a tool and an agent, and between different roles an agent can play, such as a professional, a companion, and an assistant.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Rozendaal et al (2019) ; Rozendaal et al (2020) and Ekström and Pareto (2022) have explored robotic agents (robotic ball, robotic backpack, Pepper as a social, and educational robot) playing interchangeable roles between a tool and an agent, which aligns with the design implications on the theme relating emphasized in this work. The results and design implications of this work suggest that a social robot should be able to transition between a tool and an agent, and between different roles an agent can play, such as a professional, a companion, and an assistant.…”
Section: Discussionmentioning
confidence: 81%
“…The design implications suggested in this work aim to expand this understanding, and 'understand' knowledge and intentions at different levels of activity in activity-theoretical terms, where motive and conflicts at a higher level of activity relate to intentions and underlying needs, and at the lower level of activity relate to knowledge about the facts, procedures, and social norms. Rozendaal et al (2019); Rozendaal et al (2020) and Ekström and Pareto (2022) have explored robotic agents (robotic ball, robotic backpack, Pepper as a social, and educational robot) playing interchangeable roles between a tool and an agent, which aligns with the design implications on the theme relating emphasized in this work. The results and design implications of this work suggest that a social robot should be able to transition between a tool and an agent, and between different roles an agent can play, such as a professional, a companion, and an assistant.…”
Section: Design Implicationsmentioning
confidence: 81%
See 2 more Smart Citations
“…When Pepper hears a sound, it orients itself toward the person who created the sound (claps or voice), establishing and maintaining eye contact with that person. Carros et al [16] found that Pepper's speech recognition was not always accurate with elderly people, while Ekstrom et al [17] noted that it had difficulty interacting with children. However, children were found to be motivated and engaged in the presence of Pepper [18].…”
Section: Related Workmentioning
confidence: 99%